Platelet Phenotype and Function in the Setting of Pediatric Extracorporeal Membrane Oxygenation (ECMO): A Systematic Review - Yaw, Hui Ping; Van Den Helm, Suelyn; MacLaren, Graeme; Linden, Matthew; Monagle, Paul; Ignjatovic, Vera (Frontiers in Cardiovascular Medicine, 2019)
This systematic review aims to summarize the effects of ECMO on platelets in children. Extracorporeal membrane oxygenation (ECMO) is a modified form of a heart-lung machine that aims to provide long-term heart and lung support to patients with cardiac or respiratory dysfunction. Despite 80% of ECMO occurring in the paediatric setting, the majority of research has focused on adults. This may reflect challenges in ethical approval and limited availability of blood sample volume for paediatric research. Despite its life saving effectiveness in most critically-ill children, paediatric ECMO carries a high risk of bleeding and clotting complications. Shear stress, exposure of blood to artificial surfaces associated with the intact ECMO system, polypharmacy and the critically unwell patient likely contribute to this haemostatic derangement. Changes to the number and function of blood platelets, the cellular element of the haemostatic system, is proposed to be the main cause of coagulopathy seen in patients on ECMO. However, the specific role of platelets and their contribution to the pathophysiology of clinical events has yet to be identified in paediatric ECMO patients. Current techniques used for the assessment of platelet function; complications (e.g. thrombosis, bleeding and inflammation) and therapy used (e.g. anti-platelet agents) will be discussed in details to provide an overview of the current knowledge in this vulnerable population.